Function Groups Analysis of Wood-Plastic Composite with Plasctic Waste and Pelawan’s Wood Sawdust (Tristaniopsis merguensis) - Ristika Oktavia Asriza; Diah Humaira; Sri Hawa T Insan; Zomi Zomi (Department of Chemistry - Universitas Bangka Belitung, 2019)
One of the efforts in tackling the increasingly large amount of plastic waste is to synthesize composite material from plastic waste with Pelawan’s wood sawdust (Tristaniopsis merguensis) as a raw material for the uphold of pepper plants. Pelawan is one of the endemic plants in the Bangka Belitung Islands Province. The characteristic observed in this study is the functional group of plastic waste composites with Pelawan’s wood sawdust, which was obtained from FTIR analysis. The method used in this study is to mix plastic waste and wood dust against contraper with variation ratio (wt / wt). The results of this FTIR show that there is an effect of the ratio of the amount of plastic waste and wood dust against the intensity of IR absorption. Based on IR data, the presence of absorption peak of FTIR spectrum at wave number 3327 cm-1 and widening of absorption in the region of wave number 3000-3550 cm-1 indicates the presence of O-H functional groups. The absorption band of the O-H vibrations is due to the presence of water molecules found in cellulose contained in the Pelawan’s wood sawdust. The absorption peak at wave number 1737 cm-1 indicates the existence of strain vibrations from the functional group C=O. While the absorption peak at wave number 1300-1000 cm-1 indicates the existence of stretch vibration from C-O. Therefore, the absorption tapes indicate the presence of cellulose originating from Pelawan’s wood sawdust which has been bound to plastic.